3D bioprinting for potential use in nasal cartilage reconstruction - Ruiz Cantu, Laura A. (2018)
3D printing is an additive manufacturing technique that is rapidly gaining traction in health and medical applications. This technique could potentially benefit plastic and reconstructive surgeries by fabricating patient-specific tissue replacements with tissue-like functions and mechanical properties. One specific example in the field of plastic and constructive surgery is nose reconstruction. Current gold standard for nasal reconstruction after rhinectomy or severe trauma involves a three stage surgery that requires a minimum of three and maximum of seven operations to achieve an acceptable result. The surgical procedure require transposition of autologous cartilage grafts in conjunction with coverage using an autologous skin flap. Harvest of autologous rib cartilage requires a major additional procedure which creates donor site morbidity. Additionally, major nasal reconstruction also requires sculpting autologous cartilages to form a cartilage framework, which is complex, highly-skill demanding and time-consuming.